Custer at Gettysburg : a new look at George Armstrong Custer versus Jeb Stuart in the battle's climactic cavalry charges /: a new look at George Armstrong Custer versus Jeb Stuart in the battle's climactic cavalry charges. ([2019]) - Tucker, Phillip Thomas, 1953-
No abstract available